Persecution in the book of Revelation - P. G. R. de Villiers (Acta Theologica)
In this article attention will be given to scholarly interpretations of persecution in Revelation with special attention to their theoretical, hermeneutical and theological implications. After an introductory discussion of the traditional interpretation of a “real” persecution in a Domitianic setting, attention will be given to the recent theory of “perceived” persecution and its theological implications. This is followed by critical remarks about some theoretical and hermeneutical issues. The article concludes with suggestions for an alternative approach to persecution in Revelation that is more in line with the literary nature of the book and with an accountable hermeneutics.